On Improving the Decoding of Random Codes Based On Quasigroups - Popovska Mitrovikj, Aleksandra; Bakeva, Verica; Markovski, Smile (Faculty of Computer Science and Engineering, Ss. Cyril and Methodius University in Skopje, Macedonia, 2012)
In this paper we examine the influence of the length of the messages on the performances of error-correcting codes based on quasigroup transformations proposed elsewhere. We made simulations for binary symmetric channel, for different lengths of messages with the same rate and find the packet-error probability (PER) and the bit-error probability (BER). Also we give some ideas for speed-up the decoding process and improving the performances of random codes based on quasigroups.
Keywords: error-correcting code, random code, packeterror probability, bit-error probability, quasigroup, quasigroup transformation